Plasma thyroid hormones concentrations in donkey stallions (Equus caballus) - BUGALIA, N. S; SHARMA, SATISH; GARG, S L; KUMAR, VIRENDER; CHANDER, SURESH (The Indian Journal of Animal Sciences, 2013)
Thyroid function was studied in normal libido (reaction time <5 min: n=6) and low libido donkey stallions (reaction time >30 min, n=6) at 15 days interval during breeding (july and August) and nonbreeding seasons (December and January). Sighificantly (P<0.01) elevated profiles of plasma T3 and T4 were recorded in normal libido stallions compared to low libido donkey stallions during breeding and nonbreeding seasons. Thyroid hormones registered sighnificant (P<0.01) decrease during nonbreeding season in both normal and low libido donkey stallions. However, variations in thyroid activity were nonsignificant between months during breeding and nonbreeding seasons in the 2 groups of stallions.